Sexual dimorphism in skin immunity is mediated by an androgen-ILC2-dendritic cell axis - Chi, Liang; Liu, Can; Gribonika, Inta ; 0000-0002-5694-1315; Gschwend, Julia; Corral, Dan; Han, Seong-Ji; Lim, Ai Ing; Rivera, Claudia A; Link, Verena M; Wells, Alexandria C; Bouladoux, Nicolas; Collins, Nicholas; et al. (Science (New York, N.Y.), 2024)
Males and females exhibit profound differences in immune responses and disease susceptibility. However, the factors responsible for sex differences in tissue immunity remain poorly understood. Here, we uncovered a dominant role for type 2 innate lymphoid cells (ILC2s) in shaping sexual immune dimorphism within the skin. Mechanistically, negative regulation of ILC2s by androgens leads to a reduction in dendritic cell accumulation and activation in males, along with reduced tissue immunity. Collectively, our results reveal a role for the androgen-ILC2-dendritic cell axis in controlling sexual immune dimorphism. Moreover, this work proposes that tissue immune set points are defined by the dual action of sex hormones and the microbiota, with sex hormones controlling the strength of local immunity and microbiota calibrating its tone.
Keywords: Female; Male; Androgens/metabolism; Dendritic Cells/immunology; Gonadal Steroid Hormones/metabolism; Immunity, Innate; Lymphocytes/immunology; Sex Characteristics; Skin/immunology; Animals; Mice; Mice, Inbred C57BL; Microbiota